Универсальная методика и ее место в практике анализа многофазных обмоток - Дёгтев, Владимир Григорьевич (НТУ "ХПИ", 2012)
Рассмотрены материалы одной из последних публикаций, посвященной разработке универсальной методики расчета обмоточных коэффициентов произвольных многофазных обмоток и критическому анализу ряда публикаций. Показано, что алгоритм, положенный в основу данной методики, представляет собой широко известный способ определения геометрической суммы векторов, а форма его представления в статье характеризуется рядом существенных недостатков.

The paper analyzes one of the latest publications devoted to exploration of winding factors calculation for multiphase windings with a universal calculation method and critical analysis of a number of publications. It is shown that the algorithm on which the given method is based is one of the possible variants of a well known technique for calculating vectors geometric sum and the form of its presentation in the article considered is characterized by a number of serious disadvantages.
A universal method and its place in the practice of multiphase windings analysis
Keywords: алгоритм; сумма геометрическая; сумма векторов; обзор критический; multiphase windings; winding factor; harmonic analysis; algorithm of calculation